2012
DOI: 10.1021/ol301263v
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Synthesis of Dendrimers via the Passerini Three-Component Reaction

Abstract: Tuning properties by programming the surface functional group composition of surface-block dendrimers has been limited to dendrimers with only two types of surface functionality (i.e., surface-diblock dendrimers). The Passerini reaction provides dendrimer products from precursor dendrons in reasonable yields. This proof-of-principle experiment opens the door to making surface-triblock dendrimers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 46 publications
0
70
0
1
Order By: Relevance
“…The related Passerini three‐component reaction (Passerini‐3CR), another famous IMCR, has also been successfully used in polymer science. For instance, it has been applied in the synthesis of ADMET monomers or in the synthesis of dendrimers through the convergent approach by combining functionalized precursor dendrons . More interestingly, the Passerini‐3CR was introduced as polymerization technique by using bifunctional carboxylic acids and oxo‐compounds to obtain versatile α‐amide‐substituted polyesters with high molecular weights .…”
Section: Introductionmentioning
confidence: 99%
“…The related Passerini three‐component reaction (Passerini‐3CR), another famous IMCR, has also been successfully used in polymer science. For instance, it has been applied in the synthesis of ADMET monomers or in the synthesis of dendrimers through the convergent approach by combining functionalized precursor dendrons . More interestingly, the Passerini‐3CR was introduced as polymerization technique by using bifunctional carboxylic acids and oxo‐compounds to obtain versatile α‐amide‐substituted polyesters with high molecular weights .…”
Section: Introductionmentioning
confidence: 99%
“…7 Recently, Rudick reported that a three-component Passerini coupling reaction has been efficiently utilized to generate triblock dendrimers of low generations from dendrons functionalized at the focus. 9 In contrast to convergent methods, divergent methods offer advantages in that they yield larger dendrimers, adding significant mass throughout the synthesis. Marrying the efficiency of divergent synthesis with the controlled diversity afforded by the convergent methods remains an elusive goal.…”
mentioning
confidence: 99%
“…3a gives a polymer with M n ¼ 5.9 kDa and PDI ¼ 1. 16. This polymer was pure PNIPAM as confirmed by the 1 H NMR spectrum shown in Fig.…”
Section: Resultsmentioning
confidence: 56%
“…[15] Asymmetric dendrimers have also been prepared by this reaction. [16] Our group extended the use of the Passerini reaction and developed a new MCP for preparing sequence-regulated poly(ester amide), polyamide with various functional groups, star copolymers, and photolabile polymers. [6d,17] Herein, we report for the first time the synthesis of graft copolymers from monomers without branching structures via construction of the polymer backbones by Passerinibased MCP (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%